A study on the determinants of unemployment rate in Malaysia / Nor Ayuni Mohamad Zulkifli - Mohamad Zulkifli, Nor Ayuni (2016)
This study was conducted to investigate the relationship between foreign direct investment, gross domestic product, inflation and population with unemployment rate in Malaysia. This study also is enthusiastic about revealing the most influential factor that effects unemployment rate in Malaysia. To achieve the goal of this study, the data was collected from year 1986 to 2015 yearly and was analyzed by using regression analysis. The findings show that all input variables have negative relationship between unemployment rates in Malaysia except the gross domestic product which shows a positive relationship. However, the inflation was revealed to be insignificant in influencing unemployment rate in Malaysia. Among the three remaining significant regressors, foreign direct investment was found to be the most influential factor in determining the unemployment rate in Malaysia. Generally, the overall regression model is valid and can be employed estimation purposes.